The use of mucilage extracted from Opuntia ficus indica as a microencapsulating shell - Elhleli Hanedi (Journal of the Serbian Chemical Society, 2021)
This study was aimed at investigating the micro-formulation of capsules using natural biopolymers, such as cactus mucilage (CM), carboxymethyl cellulose sodium salt (CMCNa) and chitosan (Chi) as the wall material, for the transport and supply of sunflower oil. CM samples were extracted from Opuntia ficus indica (OFI) by precipitation at different supernatant pH values (2, 4 and 12). The extracted natural polysaccharide and the resulting microcapsules were characterized by different experimental techniques. Fourier transform infrared spectroscopy analysis of the CM showed the presence of uronic acid units and sugars. Scanning electron microscopy revealed that most particles were adhered together, causing the formation of compact, linked agglomerates, which resulted in different microstructures with irregular shapes. All oil–core microcapsules were characterized, and the results showed that the different shell materials could be used to microencapsulate sunflower oil. Among them, the microcapsule crosslinked with CM and Chi was the most suitable, with the highest encapsulation efficiency (95 %). This coacervation led to the narrowest size distribution of the capsules, with diameters ranging from 1 to 5 μm. Optical microscopy confirmed the deposition of coacervate droplets around oil drops and clearly showed that the formation of coacervated particles and their deposition onto oil droplets were successive events.